Divine triads of Ancient Egypt - Sales, José das Candeias (2014)
The scheme of divine triads (associations of three deities, originally from the same city, later also from different geographic locations) is the most frequent group of deities of ancient Egypt. The formation of a triad resulted directly from the intention and interest of the priesthood(s) in establishing a link between the various cults of a particular locality or between services of different regions. The functions of the members of these groups depended entirely on the mythical or ritual context in which they were invoked and in which they justify their associations that, in all cases, was an attempt for 'unity in diversity'.